Smart cities: worldwide smart urban transportation´s scenario and importance - dos Santos, Rosana Campos; Pereira, Emmanuelle Pedroso; Barroso Castañon, José Alberto (Revista Nacional de Gerenciamento de Cidades, 2020)
Urban mobility should emphasize enough so that its efficiency encompasses the world population, besides being a notwithstanding factor to smart cities, which are basically the ones who integrate adequate utilization of resources, turn their attention to mobility and to the correct use of energy, with the main goal of improving people´s lives. This paper aims at presenting the importance and need for smart urban mobility to promote an improvement of everyone´s life quality, and a portray of smart mobility worldly scenery, which entirely impacts the cities´ constructed environment, so as so that its management should be efficient and fitting within adequate mobility plans and sustainability. The method used initiates at bibliographic review, followed by some smart cities´ analysis. Next, a qualitative and descriptive study is developed with examples of the main smart urban transportation means present in the world and how countries should fit themselves to the construction of smart cities, promoting life quality to people and adequate surveillance of sustainable development. In Brazil, all cities with more than twenty thousand inhabitants must have an urban mobility plan up till 2022 or 2023, which is equivalent to more than 30% of the country´s cities. According to the United Nations, 68% of the world population will live in urban centers until 2050. Therefore, make the cities smart is primordial, including quality mobility, that needs all people´s involvement, besides government, companies and universities for a successful construction and solidification.